Development of a thermal process for canned crab meat (Scylla serrata) in brine - Viernes, Maria Socorro; Zamora, Myrna Benita Vargas (1991.)
The objective of this study was to establish a thermal process for the canned crab meat in brine solution. In Phase I, live mud crabs (Scylla serrata) were sampled at 0, 5 and 10 hour intervals from harvest. Microbiological, physico-chemical and sensory evaluation of the meat were performed. Results showed that the mud crab harvested even after 10 hours of storage at ambient temperature (80-86°F) could still be regarded as fresh. In Phase II, the most suitable pre-thermal process brine acid treatment was selected based on sensory evaluation. The 0.6% glacial acetic acid-3% brine was found to be the most suitable pre-thermal process brine-acid treatment for mud crab meat. In Phase III, a process time-temperature combination of 25 minutes at 250°F was established for the canning of mud crab meat. The adequacy of the process was evaluated using the graphical and Patashnik meter methods. Microbiological, physico-chemical and sensory characteristics of the canned crab meat further confirmed that the process applied was adequate, wholesome and acceptable to consumers.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Canned crab meat